Re-socialization of Street Children at Open House: A Case Study in the City of Bandung, Indonesia - Saripudin, Didin; Suwirta, Andi; Komalasari, Kokom (EDUCARE, 2008)
ABSTRACT: People around the world have continually paid special attention to the issue of children problem. One of the problems is the problem of street children. The World Report of children situation has reported that there are about 30 million children living and taking care of themselves in street area. The number of street children in Asia is approximately 20 million. Indonesia is a country representing the increase of street children, especially since 1997 due to economic crisis in Indonesia. The last number recorded is 150, 000 children. Their rights as children cannot be fulfilled, either from educational aspect, physiology needs or even growth and protection needs. Street children is frequently referred to children who behave freely, wildly, cannot be regulated and involve in various criminal cases. For the reasons above, these street children need to be recovered and given protection to make them return to their right way, live normally as other children and enjoy their rights as children through re-socialization program. Re-socialization program of street children at open house must be based on knowledge and self-awareness to be able to handle every challenge and obstacle experienced in daily life. KEY WORDS: street children, re-socialization, the concept of open house and its implementation in Indonesia.Â Â Â Â Â About the Authors: Didin Saripudin, M.Si., Andi Suwirta, M.Hum., and Kokom Komalasari, M.Pd. are lecturers at the Faculty of Social Studies Education (FPIPS), Indonesia University of Education (UPI) in Bandung. They could be contacted at: saripudinupi@yahoo.com, atriwusidna@gmail.com and komsari36@yahoo.co.id Â How to cite this article? Saripudin, Didin, Andi Suwirta & Kokom Komalasari. (2008). âRe-socialization of Street Children at Open House: A Case Study in the City of Bandung, Indonesiaâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.91-102. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 5, 2008); Revised (July 5, 2008); and Published (August 17, 2008).